2019
DOI: 10.1111/tan.13413
|View full text |Cite
|
Sign up to set email alerts
|

A novel antibody combination to identify KIR2DS2high natural killer cells in KIR2DL3/L2/S2 heterozygous donors

Abstract: The killer cell immunoglobulin‐like receptor (KIR) KIR2DS2 induces natural killer (NK) cell activation upon ligation and in genetic studies is associated with protection against certain cancers and viral infections. One of the difficulties in understanding KIR2DS2 has been that ligands have been hard to define. In part, this is because the high sequence homology between KIR2DS2 and KIR2DL3/KIR2DL2 has made it difficult to make antibodies that specifically detect NK cells expressing KIR2DS2. Using transfected N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…In this study, we propose the combination of two antibodies (1127B and 143211 mAb) to separate KIR2DS1 and the two most common KIR2DL1 allele subtypes at the same time. Other studies have proposed alternative antibody strategies to separate KIR2DS1 and KIR2DL1 or KIR2DL1 alleles (4, 14); and still other combinations of commercially available antibodies can separate the KIR2DL2/2DS2 receptor pair (56).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we propose the combination of two antibodies (1127B and 143211 mAb) to separate KIR2DS1 and the two most common KIR2DL1 allele subtypes at the same time. Other studies have proposed alternative antibody strategies to separate KIR2DS1 and KIR2DL1 or KIR2DL1 alleles (4, 14); and still other combinations of commercially available antibodies can separate the KIR2DL2/2DS2 receptor pair (56).…”
Section: Discussionmentioning
confidence: 99%
“…42 No modifications to these published sequences were made, and these constructs were shown to successfully present peptides to KIR2DS2-positive NK cells. 23 The constructs were made with two previously described KIR2DS2-binding peptides: LNPSVAATL (C*0102-LNP) and IVDLMCHATF (C*0102-IVDL) and cloned in to the pIB2 expression vector ( figure 1A ). The DNA was dissolved in PBS and used to immunize KIR-Tg mice.…”
Section: Resultsmentioning
confidence: 99%
“…KIR2DS2 is an activating receptor that recognizes group 1 HLA-C molecules in combination with different viral and synthetic peptides, and we have recently shown that KIR2DS2 recognizes highly conserved flaviviruses and hepatitis C peptides with an alanine-threonine sequence at the C-terminal −1 and −2 positions of the peptide in the context of HLA-C. 18 23 Activating KIR has been associated with protective responses against cancer. Specifically, KIR haplotypes containing activating KIR confer protection against relapse of acute myeloid leukemia following bone marrow transplantation, and this has been mapped to the region of the KIR locus that contains KIR2DS2.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst T cell receptors have a tight restriction on the peptide:MHC complexes that they bind, the KIR recognize families of peptide:MHC complexes with the inhibitory KIR recognizing HLA molecules in a broad motifbased manner allowing recognition of multiple HLA class I allotypes (17,18). KIR2DS2 is an activating receptor that recognizes group 1 HLA-C molecules, in combination with different viral and synthetic peptides and we have recently shown that KIR2DS2 recognizes highly conserved flaviviruses and hepatitis C peptides with an alanine-threonine sequence at the Cterminal -1 and -2 positions of the peptide in the context of HLA-C (14,19).…”
Section: Introductionmentioning
confidence: 99%